Exploratory trial on a few aspects of Grassland Development at Deochanda Experiment Station, D.V.C. - Guha, D P; Pandey, S N (Journal of Soil and Water Conservation, 2022)
Supply of green feed to the cat- tle for a prolonged period of time is one of the steps towards protect- ing the grassland from erosion haz- ards, caused by overgrazing. With this objective in view, a few studies were undertaken at Deochanda Ex- periment Station for finding some suitable methods of grassland deve- lopment. Results of two such ex- ploratory trials conducted in this line for three years, from 1957 to 1959, have been discussed in this paper.